mTOR as regulator of lifespan, aging and cellular senescence - Weichhart, Thomas (Gerontology, 2017)
The mechanistic target of rapamycin (mTOR) network is an evolutionary conserved signaling hub that senses and integrates environmental and intracellular nutrient and growth factor signals to coordinate basic cellular and organismal responses such as cell growth, proliferation, apoptosis, and inflammation dependent on the individual cell and tissue. A growing list of evidence suggests that mTOR signaling influences longevity and aging. Inhibition of the mTOR complex 1 (mTORC1) with rapamycin is currently the only known pharmacological treatment that increases lifespan in all model organisms studied. This review discusses the potential mechanisms how mTOR signaling controls lifespan and influences aging-related processes such as cellular senescence, metabolism, and stem cell function. Understanding these processes might provide novel therapeutic approaches to influence longevity and aging-related diseases.